The WTO Trade Facilitation Agreement: consulting the private sector - Grainger, Andrew (Wolters Kluwer, 2014)
Trade facilitation concerns itself with the operational quality of the international trade environment; and has its roots in the frustrations experienced by businesses when moving goods across borders – especially with regard to inefficient border management practices and trade and customs procedures. On 7 December 2013 the WTO reached an agreement on trade facilitation. Now, with trade facilitation at the very heart of contemporary trade policy, trade diplomats are faced with the challenge of having to reach a view about the quality of trade facilitation in any given country. Subsequently, as this paper argues, dedicated institutional mechanism involving the private sector – for example, within the spirit of UN CEFACT Recommendation 4 – need to be developed. Although consultation with the private sector is not without its challenges, they would help ensure that the resources invested into trade facilitation are put to best use, and that the quality of implemented trade facilitation measures are continuously monitored and assessed.